2021
DOI: 10.1074/mcp.ra120.002384
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analyses Identify Differentially Expressed Proteins and Pathways Between Low-Risk and High-Risk Subtypes of Early-Stage Lung Adenocarcinoma and Their Prognostic Impacts

Abstract: The histopathological subtype of lung adenocarcinoma (LUAD) is closely associated with prognosis. Micropapillary or solid predominant LUAD tends to relapse after surgery at an early stage, whereas lepidic pattern shows a favorable outcome. However, the molecular mechanism underlying this phenomenon remains unknown. Here, we recruited 31 lepidic predominant LUADs (LR: low-risk subtype group) and 28 micropapillary or solid predominant LUADs (HR: high-risk subtype group). Tissues of these cases were obtained and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Moreover, high-expression ERO1A in cancers pertains to tumor cell migration and proliferation [ 18 , 22 , 40 ]. Meanwhile, ERO1A overexpression was associated with poor prognosis [ 19 , 37 ] that coincides exactly with our data. Afterward, functional experiment denoted that miR-218-5p constrained LUAD cell functions through inhibiting ERO1A expression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, high-expression ERO1A in cancers pertains to tumor cell migration and proliferation [ 18 , 22 , 40 ]. Meanwhile, ERO1A overexpression was associated with poor prognosis [ 19 , 37 ] that coincides exactly with our data. Afterward, functional experiment denoted that miR-218-5p constrained LUAD cell functions through inhibiting ERO1A expression.…”
Section: Discussionsupporting
confidence: 91%
“…Endoplasmic reticulum oxidoreductase 1 alpha (ERO1A) is an oxidortase in the endoplasmic reticulum and the primary regulator of protein disulfide isomerase (PDI) oxidation [ 14 , 15 ]. The overexpression of ERO1A in cancers, like breast cancer [ 16 ], gastric cancer [ 17 ], pancreatic cancer [ 18 ], and LUAD [ 19 ], is linked with poor prognoses of patients. Besides, ERO1A upregulation induces vascular endothelial growth factor (VEGF) expression and angiogenesis [ 20–22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al compared the transcriptomic profiles between SPA and acinar predominant adenocarcinoma and showed that SPA was enriched in pathways associated with RNA polymerase activity and p53 inactivation (7). Zhou et al performed comprehensive proteomic analyses of high-risk LUAD subtypes (micropapillary and solid) and low-risk subtype (lepidic) and found that differentially expressed proteins were enriched in pathways involved in remodeling of extracellular matrix and activation of DNA replication and cell cycle (8). Dong et al investigated the immune profiles of LUAD histologic subtypes and discovered that SPA was correlated with an immunoresistant tumor microenvironment (3).…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2015 World Health Organization Classification of Lung Cancer (3), based on prognosis, lung adenocarcinoma is classified into five histopathological subtypes. Micropapillary type is a high-risk subtype which has the potential for rapid metastasis and a poor prognosis (4,5). Micropapillary pattern (MPP) refers to the free central cluster of cells lacking fibrous vessels (6).…”
Section: Introductionmentioning
confidence: 99%